The Diagram as Paradigm Cross-Cultural Approaches - Hamburger, Jeffrey F.; Roxburgh, David J.; Safran, Linda (Dumbarton Oaks Research Library and Collection, 2022)
This is the first book that looks at medieval diagrams in a cross-cultural perspective, focusing on three regions-Byzantium, the Islamicate world, and the Latin West-each culturally diverse and each closely linked to the others through complex processes of intellectual, artistic, diplomatic, and mercantile exchange. The volume unites case studies, often of little-known material, by an international set of specialists, and is prefaced by four introductory essays that provide broad overviews of diagrammatic traditions in these regions in addition to considering the theoretical dimensions of diagramming. Among the historical disciplines whose use of diagrams is explored are philosophy, theology, mysticism, music, medicine, mathematics, astronomy, and cosmology. Despite the sheer variety, ingenuity, and visual inventiveness of diagrams from the premodern world, in conception and practical use they often share many similarities, both in construction and application. Diagrams prove to be an essential part of the fabric of premodern intellectual, scientific, religious, artistic, and artisanal life